Strategies used by farmers to cope with drought in Machakos County, Kenya - Thiongo, Karuri; Ngaira, Professor Josephine . K. W; china, Professor S (IJRDO - Journal of Applied Management Science, 2016)
Drought is defined as a prolonged and abnormally dry and hot period which causes a scarcity of water for thenormal needs of the affected community and ecosystem. It is a slow onset disaster that is believed to be the primarycause of famine due to crop failure. Droughts present a serious threat to local, national and global development. InKenya drought affects more than three-quarters of land which is arid and semi-arid. The effects of drought include;death of animals, loss of human lives, cases of malnutrition, crop failure, and famine and water scarcity. To mitigatethese effects, farmers have developed various strategies which are both indigenous and modern. Such strategiesinclude: the provision of relief food, out-migrations, destocking-restocking, remittances and donation, marketexchanges, and the provision of savings and credit facilities. However, the extent and nature of these copingstrategies have not been researched. The study was conducted in Machakos County where farmers experience alltypes of drought and the listed strategies are used. The overall objective of the study was to investigate farmerscoping strategies to drought and their implications to agricultural production. Specific objectives of the study were:to establish socio-economic characteristics of the farmers and types of farming practiced in the study area; toestablish farmers knowledge of drought and causes of drought in the study area; to evaluate drought copingstrategies used by farmers in response to drought in the study area and to examine the effect of drought copingstrategies on farm production in the study area. Both qualitative and quantitative data were collected usingquestionnaires. These included farmers’ views on whether; drought had been noticed, temperature had increased,length of seasons had changed, rainfall had decreased; and frequency of drought, coping strategies and their effectson production. Mixed research design was employed in this study. Study population included 350 small-scalefarmers randomly sampled in all the 8 sub-Counties. Collection of data was done by interviewer guidedquestionnaires and Focus group discussion guides and interview schedules. Data were analyzed using frequencies,percentages, score ranking and presented through cross tabulations, pie charts, tables and discussions. The majorfindings included: the mean household farm size being 3.05 acres. Thirty four percent (34%) earned between 6001and 20000, 23% earned between 3001 and 4500, 18% earned 1501- 3000, 15% earned 4501-6000 and 3% of therespondents earned 20001 and above, Ninety nine percent (99%) of respondents were affected by drought andEighty-six percent (86%) of respondents observed a change in the timing of rainfall. Almost half of the farmers(48%) defined drought as shortage of rain during the rainy season and twenty percent (20%) as cessation of rainduring the rainy season. Ninety two 92(%) percent of the respondents attributed planting cassava to improved farmproduction and 19% (69 farmers) recommended planting of drought resistant variety of crops. Seventy one percent(71%) said that multicropping increased farm production to a large extent. There is therefore a positive relationshipbetween the strategies used by farmers and farm production. The findings of the study are useful to agriculturalpolicy makers, government agencies dealing with drought, organizations working in drought prone areas in theirsearch for solutions to drought impacts in Kenya.